Green biomaterials and advanced technologies for road pavements - Ashimova, Saltanat Zhandarbekovna; Cerra, Maria Carmela; Rossi, Cesare Oliverio; Burkhanbaevich, Teltayev Bagdat (Università della Calabria, 2021)
The main objective aims at developing methodologies and new biomaterials for the sustainability assessment of “green bituminous mixtures”. “Green bituminous mixtures” is used in the context as a general term for all types of bituminous mixtures in which specific materials or technologies are used with the aim of reducing the environmental impact and of reducing health risks of workers. In the present research new bioadditives were developed and tested to improve the adhesion between bitumen and stones, to modify the rheological characteristic of the bitumen as well as rejuvenating properties of the bitumen.
Dottorato di Ricerca in Scienze della Vita. CICLO XXXII
Keywords: bitume; Impatto ambientale; Bio-additivi; Reologia; Ringiovanenti